Analytical Studies on the Oxidation of Nitroanilines Using Potassium Dipertellurato Cuprate (III) - Chauhan, R.P.S.; Nand Singh, Daya; Singh, V.K.; Chaurasia, P.K. (Asian Journal of Chemistry, 2010)
An accurate method has been described for the determination of o, mand p-nitroaniline with the use of potassium diperteIIurato cuprate(IIl) asthe oxidant. The sample is reacted with excess of Cu(IIl) solution at hotplate under refluxing condition for about 10 min. Af!er the reaction wasover, the contents were cooled to room temperature. The unreacted Cu(III)reagent was estimated by the Arsenite method. A blank was also run underidentical conditions using all reagents except the sample. The precisionand accuracy are within ±1%.